Kelimpahan Dan Keanekaragaman Moluska (Gastropoda Dan Bivalvia) Di Kawasan Pesisir Desa Rebo Kabupaten Bangka - Agustina, Riza; Supratman, Okto; Farhaby, Arthur M; Okto Supratman (Universitas Bangka Belitung, 2024)
The Coastal Area is an aquatic ecosystem that has high productivity and is able to support the survival of various aquatic biota and is often used as a place for various daily life activities by residents including fishing activities, tourism activities and mining activities. The aims of this study were to analyze the density, diversity, uniformity and dominance of molluscs (gastropods and bivalves) and to analyze the relationship between the density of mollusks (gastropods and bivalves) and environmental factors. The sampling technique used the 1x1m² Quadratic Transect method. The results obtained at all observation stations were 13 types of gastropods and 9 types of bivalves. Diversity is in the low to medium category which ranges from 0.8760 to 2.1655. The uniformity of gastropods and bivalves was moderate to high which ranged from 0.5291-0.8715, and was dominated by Pinerella cingulata gastropods. The results of principal component analysis (PCA) showed that the density of gastropods showed the parameters of depth, silt and clay, and the density of bivalves showed the parameters of brightness, salinity and sand which had a high affinity with density which was a limiting factor for the distribution or abundance of gastropods and bivalves.